2012
DOI: 10.1108/02634501211231883
|View full text |Cite
|
Sign up to set email alerts
|

Innovative mobile marketing via smartphones

Abstract: Purpose -Smartphone adoption by consumers is increasing exponentially, and presents marketers with many new opportunites to reach and serve customers. However, are consumers ready for mobile marketing through their smartphones? This study aims to investigate consumers' willingness to accept marketing through their smartphones. Design/methodology/approach -The study is based on an online survey of 428 respondents. The data is analyzed through ANOVA and regression analysis. Findings -The results indicate that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
117
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(142 citation statements)
references
References 48 publications
5
117
0
4
Order By: Relevance
“…This can be interpreted in a twofold manner. First, our results support other researchers' statements about the use of smartphones in digital marketing, which claim that the existing gap is narrowing, as more consumers from all age groups embrace mobile marketing through increased smartphone penetration [72]. A second interpretation, complementary to the previous one, involves older generations' perceptions of the utility value of mobile devices.…”
Section: Discussionsupporting
confidence: 76%
“…This can be interpreted in a twofold manner. First, our results support other researchers' statements about the use of smartphones in digital marketing, which claim that the existing gap is narrowing, as more consumers from all age groups embrace mobile marketing through increased smartphone penetration [72]. A second interpretation, complementary to the previous one, involves older generations' perceptions of the utility value of mobile devices.…”
Section: Discussionsupporting
confidence: 76%
“…Finally, additional research should investigate how a combination of mobile touch points (eg a coupon for a free item, mobile ordering and mobile payment) influences food purchasing decisions. 42 Parents more engaged than non-parents In-store technology…”
Section: Segments and Mobile Behaviourmentioning
confidence: 99%
“…Barnes & Scornacca (2004) contended that the majority of mobile marketing services are based on short message service (SMS) which is based on simple push-based practices. Based on these practices by business organizations, Persaud & Azhar (2012) noted that future research is needed to gain clearer insights into how consumers will react to this type of marketing strategy technique considering the capabilities of modern smartphones with global positioning systems. Grant & O'Donohoe (2007) revealed that five key factors influence consumers to use mobile phones.…”
Section: Mobile Marketingmentioning
confidence: 99%
“…Karjaluoto, Lehto, Leppaniemi, & Jayawardhena (2009), for example, observed that mobile marketing is still in its early stages, and mobile marketing practices likely to go through fundamental changes as the technological applications continues to evolve. Persaud & Azhar (2012) further stress that research in mobile marketing is in its early stages, however, the literature is growing. In response to these research gaps and future investigation, this study, therefore, aims to reveal past empirical evidence to examine the influence of customer trust and privacy concerns as they affect consumers' purchase decision with regards to mobile marketing.…”
mentioning
confidence: 99%
See 1 more Smart Citation